ANALISIS TEKS MEDIA SURAT KABAR “KEDAULATAN RAKYAT DAN JAWA POS” TERKAIT KASUS KEKERASAN SEKSUAL TERHADAP PEREMPUAN DAN ANAK - Nanda Syukerti; Ruhul Auliya; Alvina Anggarkasih (Jurnal Ilmu Komunikasi Balayudha, 2021)
Sexual violence against women and children is still happening in Indonesia. Indonesia is a sexual violence emergency country that requires special attention from the government or other institutions so that this can be overcome together. Many efforts have been made by various women's and child protection institutions to prevent this from happening. Apart from the government and NGOs, the media, in this case, of course, also participates in the news as a media that can provide protection, but in reality there is still a lot of news that corners and does not provide protection for women and children. To prevent the recurrence of sexual violence against women and children, the role and participation of the community is needed. One component of the community is the family, which plays a role in instilling knowledge in children from an early age. This essay aims to discuss the emergency situation of violence in Indonesia and the role that non-governmental organizations can play in preventing sexual violence through campaigns, discussions and knowledge sharing through radio media, social activities, publishing books and assisting in the resolution process.